The Role of Communication in Conflict Resolution on Twitter Social Media - Mikhael Yulius Cobis; Jamalullail Jamalullail (Budapest International Research and Critics University, 2022)
Basically, conflicts arise due to differences of opinion, goals and interests. So, to deal with conflict situations requires a deep understanding of the implementation of conflict resolution and good communication. This study aims to identify and analyze the role of communication in resolving conflicts that occur on Twitter social media, which provides space for users to freely express their opinions, but has the potential for conflict to arise. This study uses a descriptive qualitative method based on the constructivism paradigm, and uses the concept of conflict communication theory which examines the concepts of communication theory and social conflict. The research findings reveal that communication has an important role and has an impact on the success of conflict resolution on Twitter social media. One form of effective conflict resolution to deal with conflicts on Twitter social media is a coalition, by inviting the parties involved to discuss. Although communication has gaps to create conflict, good communication can be one way to avoid conflict escalation and achieve peace.